Analisis Tabu List Length Pada Penjadwalan Perkuliahan - Rayuwati, Rayuwati (Universitas Malikussaleh, 2014)
Scheduling classes is a set of process management in the form of lectures in courses that are organized in a set period and a set of lecture rooms as well as a lecturer. The process of scheduling lectures crafted by meeting a number of constraint defined with the aim to produce a more optimal schedule of classes. Tabu search algorithm is an optimization method based on local search. The search process moves from one solution to the next solution, by choosing the best solution from the current solution neighborhood (current) is not classified as a solution forbidden (tabu). Fundamental memory structures in tabu search called tabu list. Tabu list storing attributes of partial move (transition solution) that has been applied to the previous iteration-iteration. Tabu search algorithm is influenced by several parameters, one of which is the size of the taboo list. The size of the taboo list alagoritma tabu search will affect the number of iterations and time required to produce a more optimal schedule of lectures.Â